Comparison of Human Resource Management (HRM) Strategies between Labuan Bajo Tourism Business and Dili Timor Leste Tourism Business Based On 7s-Mckinsey - do Ceu Fatima, Arlindo; Churiyah, Madziatul (Greenation Research & Yayasan Global Resarch National, 2024)
This study compares how Labuan Bajo, Indonesia, and Dili, Timor Leste's tourism businesses manage their human resources using the 7S-McKinsey framework. This framework analyzes seven elements: shared values, strategy, structure, systems, leadership style, staff, and skills. The research reveals differences in HRM approaches. Labuan Bajo prioritizes environmental sustainability and a structured training system, while Dili focuses on tourism promotion and informal learning. Labuan Bajo has a more formal organizational structure and a consultative leadership style than Dili's flexible and authoritative leadership structure. In conclusion, this study highlights the distinct advantages and disadvantages of Labuan Bajo and Dili in their HRM practices and provides valuable insights for the tourism industry. By understanding the factors influencing success in tourism HR, this research can guide the development of more effective practices, making it a practical resource for HR professionals and policymakers.